Influence of Socioeconomic Opportunity Disparities on Sex/Gender Inequalities in Cognitive Decline. (20th December 2022) - Avila, Justina F; Seblova, Dominika; Turney, Indira C; Schupf, Nicole; Mayeux, Richard; Brickman, Adam M.; Manly, Jennifer J
Abstract: Background: State‐level socioeconomic opportunity disparities have been linked to health outcomes. We examined whether early‐life exposure to state‐level socioeconomic opportunity disparities between women and men influences the pattern of sex/gender inequalities in cognitive decline. Method: Participants were 2, 394 U.S.‐born non‐Latinx Black and non‐Latinx White women and men enrolled in the Washington Heights/Inwood Columbia Aging Project (WHICAP), who were dementia free at their baseline study visit. Age at first cognitive assessment ranged from 61‐101 and the average follow‐up time was 4.8 years. Cognitive outcomes were level and trajectory on memory and language scores. A socioeconomic opportunity disparity index (SODI) was created using census data on sex/gender disparities in labor force participation, occupational status, and educational attainment between the years 1900 to 1960 (birth year range for WHICAP participants). The SODI ranged from 0 to 1, with higher scores reflecting wider sex/gender disparities in socioeconomic opportunities. SODI values were linked to WHICAP individual data via birth year and state. Multiple‐group growth curve modeling was used to examine interactions between sex/gender and SODI on cognitive trajectories across racial groups. All models accounted for age, childhood SES, and state of birth, as well as differential study attrition due to death. Result: Smaller disparities in state‐level opportunity were associated with 1) higher baseline cognitive test performance across groups and 2) slower memory and language decline for Black women and White women and men. Women demonstrated an advantage over men on cognitive measures and we expected women's advantage to be more pronounced in states with lower opportunity disparities. This pattern held true for Black individuals with regards to memory and language level and for memory decline among White individuals. However, White women's advantage over White men on baseline memory was more pronounced in states with higher opportunity disparities. Conclusion: Being born in a state where socioeconomic opportunities were more equally distributed among women and men was positively linked to cognitive outcomes later in life. Our results suggest that this relationship varies across men and women depending on their race, contributing to different patterns of sex/gender inequalities in late‐life cognitive trajectories.